Effects of ketamine and midazolam on resting state connectivity and comparison with ENIGMA connectivity deficit patterns in schizophrenia. Issue 3 (21st October 2019) - Adhikari, Bhim M.; Dukart, Juergen; Hipp, Joerg F.; Forsyth, Anna; McMillan, Rebecca; Muthukumaraswamy, Suresh D.; Ryan, Meghann C.; Hong, L. Elliot; Eickhoff, Simon B.; Jahandshad, Neda; Thompson, Paul M.; Rowland, Laura M.; et al.
Abstract: Subanesthetic administration of ketamine is a pharmacological model to elicit positive and negative symptoms of psychosis in healthy volunteers. We used resting‐state pharmacological functional MRI (rsPhfMRI) to identify cerebral networks affected by ketamine and compared them to the functional connectivity (FC) in schizophrenia. Ketamine can produce sedation and we contrasted its effects with the effects of the anxiolytic drug midazolam. Thirty healthy male volunteers (age = 19–37 years) underwent a randomized, three‐way, cross‐over study consisting of three imaging sessions, with 48 hr between sessions. A session consisted of a control period followed by infusion of placebo or ketamine or midazolam. The ENIGMA rsfMRI pipeline was used to derive two long‐distance (seed‐based and dual‐regression) and one local (regional homogeneity, ReHo) FC measures. Ketamine induced significant reductions in the connectivity of the salience network (Cohen's d : 1.13 ± 0.28, p = 4.0 × 10 −3 ), auditory network ( d : 0.67 ± 0.26, p = .04) and default mode network (DMN, d : 0.63 ± 0.26, p = .05). Midazolam significantly reduced connectivity in the DMN ( d : 0.77 ± 0.27, p = .03). The effect sizes for ketamine for resting networks showed a positive correlation ( r = .59, p = .07) with the effect sizes for schizophrenia‐related deficits derived from ENIGMA's study of 261 patients and 327 controls. Effect sizes for midazolam were not correlated with the schizophrenia pattern ( r = −.17, p = .65). The subtraction of ketamine and midazolam patterns showed a significant positive correlation with the pattern of schizophrenia deficits ( r = .68, p = .03). RsPhfMRI reliably detected the shared and divergent pharmacological actions of ketamine and midazolam on cerebral networks. The pattern of disconnectivity produced by ketamine was positively correlated with the pattern of connectivity deficits observed in schizophrenia, suggesting a brain functional basis for previously poorly understood effects of the drug.